Kemampuan Memahami Persamaan Reaksi Kimia Di Era Pembelajaran Digital Pada Siswa Kelas X Mipa SMAN 5 Palangka Raya - Seliwati, Seliwati (LPPM Universitas Negeri Jakarta, 2021)
Distance learning is carried aut in order to prevent the spread and transmission of COVID-19 in the educational unit environment. The Ministry of Education and Culture has taken a policy to close schools during the COVID-19 pandemic. To overcome distance learning problems, teachers must prepare a distance learning implementation plan using digital learning media. This study aims to desribse the ability of class X MIPA students of SMA Negeri 5 Palangka Raya in understanding the concept of chemical reaction equations using digital learning media. The research method used is descriptive method with research subjects 136 students of class X MIPA SMA Negeri 5 Palangka Raya in the academic year 2020/2021. The instrument use a multiple choice written test with four answer choices and interviews. The average percentage of students’ ability to understand the concept of chemical reaction equations in indicator (1) explaining the meaning of chemical reaction equation is 62,5%; (2) determine the chemical reaction equation of the reacting substances 68,87%; (3) determine the appropriate reaction coefficient to balance the chemical reaction equation 75%; (4) determine the correct chemical compound and reaction coefficient to complete the chemical reaction equation 71,8 %. Keywords: Ability, Understand, Reaction Equation, Digital Learning.